Estudios ornitológicos en Loreto, Perú: notas sobre su historia - Salinas, Letty (2021)
In 1542 Orellana arrived in the Amazon and began a history of continuous exploration of Loreto. However, the birds’ study of Loreto began in the 19th century with the explorations of Johann Baptist von Spix, Johann Jakob von Tschudi, Francis-Louis de Castelnau, Emile Deville, Edward Bartlett, John Hauxwell and Henry Walter Bates, who collected for European and American museums. In 1850 Antonio Raimondi arrived in Peru, joining the Universidad Nacional Mayor de San Marcos, and starting national studies of birds of Loreto in 1859 and 1869. Raimondi actively collaborated with Władysław Taczanowski, assisted by Konstanty Jelski and Jan Stolzmann, whose collections in Loreto were used in Ornithologie du Pérou, the first treatise on Peruvian avifauna. Some of these specimens are preserved in the Museo de Historia Natural of the UNMSM (MHN). At the beginning of the 20th century, Malcolm Anderson and Wilfred Osgood and later the Olalla brothers collected for American museums, marking the beginning of American predominance in ornithology in Peru. The Peruvian researcher Javier Ortiz de la Puente, the first head of the Bird Section of the MHN, collected in Loreto in 1948 and 1952, before his unfortunate death. María Koepcke, next head of the MHN Bird Section, collected in Pacaya-Samiria in 1967. John Patton O'Neill visited Loreto in 1963, initiating an interest that would lead him to promote ornithology in Peru for several decades. The continuous research of Loreto's avifauna turned this region into a key point to understand the diversification patterns of Amazonian birds.